The photographic eye: the camera in recent Australian fiction - Genoni, Paul (2002)
This paper examines the frequent use of tropes derived from photography in recent Australian fiction. It suggests that the importance of photography to contemporary novelists is it's capacity to render a moment in time immutable, and it argues that photography is replacing mapping as the key strategy for representing postcolonial space. The paper concludes by providing brief readings of the nexus between time and photography in three novels; Gerald Murnane's The Plains, Liam Davison's Soundings, and Thea Astley's Reaching Tin River.